Low velocity impact resistance of thin and toughened carbon fibre reinforced epoxy. (10th November 2022) - Klingler, Andreas; He, Qinghao; Wetzel, Bernd; Allen, Tom; Ye, Lin; Breuer, Ulf
Abstract: This study investigates the effect of core-shell rubber nanoparticle and block copolymer matrix modifications on the low velocity impact resistance of thin (∼1.6 mm), multi-axial carbon fibre reinforced epoxy laminates. The results demonstrate a strongly enhanced damage resistance predominantly to impact energies of 9 J and 13 J. Lower impact energies do not sufficiently activate the energy dissipating capabilities of the applied toughening agents. In the case of 9 J impacts, it is found that the damage resistance increases with increasing modifier concentration by a successive reduction of the indentation depth. Once the impact causes large-scale fibre fracture (13 J), the damage mode changes and an increasing matrix toughness leads to a strong reduction of the damage area. However, a proper bonding between matrix and the embedded fibres is a mandatory precondition to take advantage of a core-shell rubber and block copolymer toughened matrix. Graphical abstract: Image 1